Intelligent Replication Technique for Cloud; based on K-Means Clustering (International Journal of Advanced Research in Computer Science, 2017)
The K-Means is much useful clustering algorithmic rule that has been with success applied to a wide selection of issues. However, its application has typically been restricted to little datasets. The cloud development is quickly changing into a very important service in web computing. Infrastructure as a Service (IaaS) in cloud computing is one among the foremost vital and quickest growing field. during this service model, cloud suppliers provide resources to users/machines that embody computers as virtual machines, raw (block) storage, firewalls, load balancers, and network devices. A lot of researchers had planned several techniques for intelligent replication theme. To boot to vary aware replications some parameters like energy consumption, network usage and SLA square measure taken in thought. Within the present paper, there is associate analytical survey on the K-Means cluster based totally Intelligent Replication Approach for Cloud. Throughout this approach replication of every block of the content is finished on fully completely different locations such all of those mustn't fall in varied prone locations. All the untrustworthiness of this approach depends on classification and analysis for locating safe and varied prone locations.Keywords: Cloud, Clustering, Intelligent Replication, K-means.